2001
DOI: 10.1034/j.1600-0684.2001.300208.x
|View full text |Cite
|
Sign up to set email alerts
|

A spontaneously occurring mammary gland ductal carcinoma in situ in a rhesus macaque (Macaca mulatta) and a review of spontaneous mammary gland tumors in rhesus monkeys

Abstract: A spontaneous mammary gland ductal carcinoma in situ was diagnosed in a 6-8-year-old female rhesus macaque (Macaca mulatta). To our knowledge, this is only the tenth case of spontaneous mammary gland tumors to be reported in rhesus monkeys. Despite the paucity of case reports, several theories exist to explain the occurrence of mammary tumors. The Mason Pfizer monkey virus, a type D retrovirus similar to the virus that causes simian acquired immunodeficiency syndrome, has been implicated as a possible etiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Neoplasia of the breast in the macaque has become recognized more frequently over the last decade. To date, recognized cases in both rhesus and cynomolgus macaques range from ductal hyperplasia, atypical ductal hyperplasia, lobular carcinoma in situ, ductal carcinoma in situ, and invasive ductal carcinoma Cohen et al, 2001;Wood et al, 2006). Comedo patterns in a rhesus mammary carcinoma have also recently been described (Smith et al, 2005).…”
Section: Neoplasia Of the Integument And Breastmentioning
confidence: 95%
“…Neoplasia of the breast in the macaque has become recognized more frequently over the last decade. To date, recognized cases in both rhesus and cynomolgus macaques range from ductal hyperplasia, atypical ductal hyperplasia, lobular carcinoma in situ, ductal carcinoma in situ, and invasive ductal carcinoma Cohen et al, 2001;Wood et al, 2006). Comedo patterns in a rhesus mammary carcinoma have also recently been described (Smith et al, 2005).…”
Section: Neoplasia Of the Integument And Breastmentioning
confidence: 95%
“…Lesions associated with this may include cystic endometrial hyperplasia, squamous metaplasia of the cervix, and mammary hyperplasia. Spontaneous mammary and endometrial neoplasia was reported to arise in two female macaques following a 12‐month period of constant estrus (Cohen et al, 2001; Shaw et al, 1989).…”
Section: Ovarian Cystsmentioning
confidence: 99%
“…Coarse calcification, visible on radiographs, and concentric stromal fibrosis with mild mononuclear inflammatory cell infiltrates are common. A cribriform pattern with multiple regular and evenly distributed small sieve‐like spaces may also be present (Cohen et al, 2001; Tekeli and Ford, 1980). A micropapillary pattern consists of disorganized bulbous luminal epithelial projections without a fibrovascular core, often forming complex intra‐ductal patterns (Fig.…”
Section: Hyperplastic and Neoplastic Lesionsmentioning
confidence: 99%
“…There have been about 30 reported mammary gland neoplasms occurring in nonhuman primates (1,2,6,7,9,10,14,21,23). However, there have been no documented cases of malignant myoepithelioma in the mammary gland of cynomolgus monkeys.…”
Section: Introductionmentioning
confidence: 99%